Confirmation and Keplerian motion of the gap-carving protoplanet HD 169142 b. Issue 1 (4th April 2023) - Hammond, Iain; Christiaens, Valentin; Price, Daniel J; Toci, Claudia; Pinte, Christophe; Juillard, Sandrine; Garg, Himanshi
ABSTRACT: We present the re-detection of a compact source in the face-on protoplanetary disc surrounding HD 169142, using VLT/SPHERE data in YJH bands. The source is found at a separation of 0_.^′′ 319 (∼37 au) from the star. Three lines of evidence argue in favour of the signal tracing a protoplanet: (i) it is found in the annular gap separating the two bright rings of the disc, as predicted by theory; (ii) it is moving at the expected Keplerian velocity for an object at ∼37 au in the 2015, 2017, and 2019 data sets; and (iii) we also detect a spiral-shaped signal whose morphology is consistent with the expected outer spiral wake triggered by a planet in the gap, based on dedicated hydrodynamical simulations of the system. The YJH colours we extracted for the object are consistent with tracing scattered starlight, suggesting that the protoplanet is enshrouded in a significant amount of dust, as expected for a circumplanetary disc or envelope surrounding a gap-clearing Jovian-mass protoplanet.